Organized Corporate Crimes using Model Law Development for Health Regulation and Policy - Llarena, Zharama (LSPR Institute of Communication & Business, 2022)
Corporate Governance is a conceptual framework of business designs intended to illustrate the various activities of a company towards fulfilling its profit goals as private stakeholder and contributing to public interests for social obligation of sustainable development. Tax aggressiveness is utilized by board director and its members to lessen tax contribution which is contrary to the government sector goals of maximizing tax impositions for public welfare and safety. Unlawful behavior on tax aggressiveness is known as tax evasion while tax avoidance is not a violation and serves as a loophole to the taxation system, although corporate fraud is apparent in off-label medicines. UNCITRAL model law is a legal arbitration concept of making “commercial” expand to other comparable jurisdiction of international trade. The European Patent Commission is the legal authority that delineates medical policies from patented products. This paper aims to develop arbitration framework based on stakeholder theory of corporate governance to separate tax evasion from tax avoidance as crime sourcing treatment of policies and engineer tax planning to divide intellectual property of product design with corporate fraud concerning off-label medicines. Therefore, organized crimes in pharmaceutical industries are needed to be clearly managed by institutional healthcare companies for promoting economic success.